Condition Monitoring and Performance Degradation of Civil Structures Including Fatigue Effects on Offshore Wind Turbine Support Structures - Nozari, Amin. (Tufts University. Tisch Library., 2020)
Thesis (Ph.D.)--Tufts University, 2020.; Submitted to the Dept. of Mechanical Engineering.; Advisor: Daniel Kuchma.; Committee: Jason Rife, Masoud Sanayei, Eric Hines, and Andrew Myers.; Keywords: Mechanical engineering, and Civil engineering.